Anti-Social Behaviour in Assisted Children at LPKA Class I Kupang - SEU, MEYKE ASTUTI YEMIMA; Aipipidely, Diana; Takalapeta, Theodora (Journal of Health and Behavioral Science, 2024)
This research aims to describe the factors that trigger the emergence of anti-social behaviour and forms of anti-social behaviour in assisted children of LPKA Class 1 Kupang. This study uses a qualitative method. Five people took part in the investigation. Data validity testing was performed through triangulation. Two themes were found in this research: factors in the development of anti-social behaviour and forms of anti-social behaviour. Research shows that anti-social behaviour in children in care is caused by factors that originate within the individual, also known as internal and external factors or those that originate from outside the individual (the environment). Internal factors leading to anti-social behaviour are aggression, curiosity, fear of exclusion, satisfaction/happiness, and lack of regret. External factors that can lead to anti-social behaviour include unhealthy relationships from the participant's environment, such as family, social friends, and social/community environment. This means that relationships with people around him can influence a person so much that they become a factor in developing anti-social behaviour. The forms of anti-social behaviour among children in care are very diverse, such as physical violence, sexual violence, verbal violence, illegal running, theft, and alcohol abuse.